PENGARUH DISIPLIN KERJA, KOMPETENSI DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI PEGAWAI SEBAGAI VARIABEL INTERVENING PADA DIREKTORAT JENDERAL TANAMAN PANGAN - Anggeraini, Masrurroh; Adnyana, I Made (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
Human resource management (HRM) is an important aspect in an organization that influences employee performance. In the context of the Directorate General of Food Crops, there are several problems that affect employee performance, including work discipline that is not yet strict, employee competency that is not appropriate, and less effective communication between employees. This research aims to determine the influence of work discipline, competence and communication on employee performance with motivation as an intervening variable. The research sample was 120 employees at the Directorate General of Food Crops using the Hair formula. The research approach is a quantitative method. Data collection techniques were carried out using interviews and closed questionnaires with a Likert scale of 1 to 5 with data analysis techniques using Smart PLS 3. The research results showed that there was a positive and significant influence of work discipline on employee performance, but competency did not have a significant influence on employee performance. Meanwhile, communication has a positive and significant influence on employee performance. Work discipline is also proven to have a positive and significant influence on employee motivation, but competence does not have a significant influence on motivation. Communication is also proven to have a positive and significant influence on employee motivation. Furthermore, work discipline, competence and communication also have a positive and significant influence on employee performance through motivation as an intervening variable. Based on the results of this research, several suggestions that can be made are the need to increase the application of stricter work discipline, develop employee competencies in accordance with job demands, and improve communication between employees to improve overall performance. Efforts are also needed to provide appropriate motivation to employees as a driving force in improving their performance.